Mating-induced prolactin surge is not required for subsequent neurogenesis in male mice - Smiley, Kristina O.; Phillipps, Hollian R.; Fang, Chenyun; Brown, Rosemary S. E.; Grattan, David R. (Frontiers in Behavioral Neuroscience, 2023)
Parenting involves major behavioral transitions that are supported by coordinated neuroendocrine and physiological changes to promote the onset of novel offspring-directed behaviors. In comparison to maternal care, however, the mechanisms underlying the transition to paternal care are less understood. Male laboratory mice are predominantly infanticidal as virgins but show paternal responses 2 weeks after mating. Interestingly, males show a mating-induced surge of prolactin, which we hypothesized may be involved in initiating this behavioral transition. During pregnancy, prolactin stimulates olfactory bulb neurogenesis, which is essential for maternal behavior. Mating induces olfactory bulb neurogenesis in males, but it is unknown whether this is driven by prolactin or is important for subsequent paternal care. New olfactory neurons are generated from cells in the subventricular zone (SVZ) and take about 2 weeks to migrate to the olfactory bulb, which may account for the delayed behavioral change in mated males. We investigated whether mating increases cell proliferation at the SVZ. Males were either mated, exposed to receptive female cues, or left alone (control) and injected with Bromodeoxyuridine (BrdU, a marker of cell division). Contrary to our hypothesis, we found that mating decreased cell proliferation in the caudal lateral portion of the SVZ. Next, we tested whether prolactin itself mediates cell proliferation in the SVZ and/or new cell survival in the olfactory bulb by administering bromocriptine (prolactin inhibitor), vehicle, or bromocriptine + prolactin prior to mating. While suppressing prolactin had no effect on cell proliferation in the SVZ, administering exogenous prolactin resulted in significantly higher BrdU-labeled cells in mated but not virgin male mice. No effects of prolactin were observed on new olfactory cell survival. Taken together, prolactin may have context-dependent effects on new cell division in the SVZ, while other unknown mechanisms may be driving the effects on new olfactory cell survival following mating.